The Influences Of Service Quality And Product Innovation On Service Quality (Survey Of Sonsumers At The Rizky Shop Rajapolah Tasikmalaya Regency) - Fauziah, Hamidah; Fitriadi, Budhi Wahyu; Oktaviani, Nita Fauziah (Jurnal Pusat Manajemen, 2024)
This research aims to determine the simultaneous and partial influence of service quality and product innovation on consumer satisfactionat the Rizky Shop Rajapolah Tasikmalaya regency. The method usedin this research methodwith a survey approach. The sampling technique used was incidental sampling and samples taken were 100 respondents. The analytical tool used is the multiple linear regression equation. The research results show that service quality and product innovation si,ultaneously have a significanteffect on consumer satisfaction at the Rizky Shop Rajapolah store. Servive quality partially has a significant effect on consumer satisfaction at the Rizky Shop Rajapolah store. Product innovation partially has a significant effect on consumer satisfaction at the Rizky Shop Rajapolah store Tasikmalaya district.